The anaerobic power assessment in crossfit® athletes: An agreement study - Ponce-García, Tomás; Benítez-Porres, Javier; García-Romero, Jerónimo; Castillo-Domínguez, Alejandro; Alvero-Cruz, José Ramón (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Anaerobic power and capacity are considered determinants of performance and are usually assessed in athletes as a part of their physical capacities’ evaluation along the season. For that purpose, many field tests have been created. The main objective of this study was to analyze the agreement between four field tests and a laboratory test. Nineteen CrossFit® (CF) athletes were recruited for this study (28.63 ± 6.62 years) who had been practicing CF for at least one year. Tests performed were: (1) Anaerobic Squat Test at 60% of bodyweight (AST60); (2) Anaerobic Squat Test at 70% of bodyweight (AST70); (3) Repeated Jump Test (RJT); (4) Assault Bike Test (ABT); and (5) Wingate Anaerobic Test on a cycle ergometer (WG). All tests consisted of 30 s of max effort. The differences among methods were tested using a repeated-measures analysis of variance (ANOVA) and effect size. Agreement between methods was performed using Bland–Altman analysis. Analysis of agreement showed systematic bias in all field test PP values, which varied between-110.05 (AST60PP—WGPP) and 463.58 (ABTPP—WGPP), and a significant proportional error in ABTPP by rank correlation (p < 0.001). Repeated-measures ANOVA showed significant differences among PP values (F(1.76,31.59) = 130.61, p = < 0.001). In conclusion, since to our knowledge, this is the first study to analyze the agreement between various methods to estimate anaerobic power in CF athletes. Apart from ABT, all tests showed good agreement and can be used interchangeably in CF athletes. Our results suggest that AST and RJT are good alternatives for measuring the anaerobic power in CF athletes when access to a laboratory is not possible. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Ejercicio físico - Aspectos fisiológicos; Anaerobiosis; Athletes; Ergometry; Exercise Test; Humans; Posture